Vibration modelling with optimized complex boundary in full-scale elastic theory for large end-winding - Wang, Ting; Qin, Qiyong; Zhao, Yang; Fan, Ye; Deng, Congying; Lu, Sheng (Archive of applied mechanics (1991), 2025)
This study presents a high-fidelity modelling and vibration analysis framework for a 600 MW turbo-generator stator end winding, integrating composite materials theory and discrete element methods. The double-layered winding is modelled as a conical shell model with ring and stringer stiffeners representing supporting components. Natural and forced vibration equations are derived using the Rayleigh–Ritz method with an enhanced Fourier series, enabling accurate simulation of complex elastic boundary conditions. The model is extended to optimize the stator-winding characteristic equation, yielding a semi-analytical solution for spring stiffness configuration. Key innovations include the analytical derivation of modal parameters, a rigorously formulated frequency response function, and the introduction of Rayleigh damping and excitation force potential energy. Multidimensional displacement response analysis demonstrates strong agreement with finite element results, validating the proposed equivalent digital mechanism model’s accuracy and robustness.